TD-LTE Coverage Planning Targets and UL/DL Subframe Configuration - Qiuxiang Li; Xiaodong Xu; Baihui Zhou (Dianxin kexue)
Common reference signal received power（CRS RSRP）and signal interference noise ratio（CRS SINR）are two important wireless network planning factors，which are directly related to indoor deep coverage and edge data rate. Besides，TD-LTE has flexible UL/DL configuration for different requirements of UL/DL throughput. The influences of different planning CRS RSRP and SINR targets on network performance and the relationship between CRS RSRP and SINR were mainly analyzed based on same frequency networking；UL/DL configuration for different bands was recommended after analyzing TD-LTE subframe structure as we11.